Studi Kasus Learned Optimism dalam Membantu Wanita Dewasa Penyintas Kekerasan dalam Pacaran - Meilinda, Anggela; Kristinawati, Wahyuni (Universitas Batanghari Jambi, 2024)
The aim of this research is to find out the picture of learned optimism in early adult women who are survivors of dating violence. Learned optimism is a concept that focuses on an individual's ability to develop a positive outlook and overcome challenges in a more constructive way. This research uses a case study involving two early adult female participants, data was collected through interviews and naturalistic observation. The research results show that the application of learned optimism such as positive thinking significantly helps in reducing the negative influence of the violence experienced. The picture of learned optimism that emerges is efforts to stop violence, belief that violence will end, not focusing on one problem, generalization of optimism, efforts to escape violence. Apart from that, social support from the environment also plays an important role in forming learned optimism.